Pengaruh Pelayanan Kesehatan Reproduksi terhadap Pelayanan Kegawatdaruratan Ibu - Handi Rustandi; Danur Azisssah Roesliana SOfais; Yalta Hasanudin; Fery Surahman Saputra (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Maternal health is a crucial indicator of a country's health care system and development progress. Despite global progress in maternal health services, Indonesia still faces significant challenges, particularly in areas like Bengkulu City, where gaps in maternal emergency care persist. These challenges, including delayed response to obstetric emergencies and inadequate training of health workers, contribute to preventable maternal morbidity and mortality. Purpose: To assess the impact of reproductive health services on maternal emergency care by comparing the service systems of two hospitals. Method: This was a comparative quantitative study using a quasi-experimental approach. Data were collected from 32 pregnant women receiving maternal health services at two hospitals in Bengkulu City: Tiara Sella Regional Hospital and Ummi Regional Hospital. Participants were selected using simple random sampling, and data were analyzed using inferential biostatistics, including t-tests, to examine the relationship between service quality and maternal emergency outcomes. The study focused on service accessibility, quality, early detection, and intervention protocols. Results: Results showed a significant increase in participant satisfaction after treatment, with the mean satisfaction score increasing from 1.20 to 2.90 (p = 0.001). Analysis revealed a moderate positive correlation (0.50) between pre- and post-treatment satisfaction, indicating that the intervention was highly effective for those with lower baseline satisfaction. Furthermore, there was a 6.9-point difference in mean satisfaction, with a 95% confidence interval ranging from 1.8 to 11.73. Conclusion: This study demonstrates that appropriate interventions can significantly improve patient satisfaction. There was a significant difference before and after treatment. Even patients who were initially dissatisfied benefited from the intervention. This suggests that a patient-centered approach to care can help address diverse needs and improve healthcare outcomes.